CORRECTION OF THE GUMMY SMILE THROUGH ORTHODONTICS: AN INTEGRATIVE LITERATURE REVIEW. (REMUNOM, 2023)
Introduction: Excessive gum exposure while smiling is a growing concern due to its impact on aesthetics and self-esteem. In this context, dentistry offers both surgical and non-surgical treatments to improve this condition. Objective: In this context, the present study aims to elucidate orthodontics as an option for the treatment of the gummy smile. Methodology: For our study, the search strategy "((“Smiling” AND “Gingiva”) OR (“Gummy smile”)) AND (“Orthodontics, Corrective”)” was developed and replicated in electronic health databases: Pubmed, Web of Science, Cochrane Library, Scopus, and Embase. Articles published in the last 10 years, regardless of their study design or publication language, were reviewed if they related gummy smile and orthodontics, excluding studies where surgery was used exclusively for gummy smile correction. Results: Four articles were analyzed, all of which were case reports in which orthodontics was performed using mini-implants for gummy smile correction. Unjustified refusals for correction with orthognathic surgery were noted. One report used gingivoplasty following orthodontics for an ideal aesthetic outcome. Conclusion: It is concluded that orthodontics is effective in correcting this problem, especially when combined with the use of mini-implants. However, it is worth noting that orthodontics is more commonly used as a complement in patients already requiring orthodontic correction, while crown lengthening surgeries are the primary choice in isolated cases of gummy smile.